2013
DOI: 10.1016/j.dental.2013.08.207
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance of novel bioactive glass containing dental restorative composites

Abstract: Objectives Bioactive glass (BAG) is known to possess antimicrobial properties and release ions needed for remineralization of tooth tissue, and therefore may be a strategic additive for dental restorative materials. The objective of this study was to develop BAG containing dental restorative composites with adequate mechanical properties comparable to successful commercially available composites, and to confirm the stability of these materials when exposed to a biologically challenging environment. Methods C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 52 publications
7
80
1
4
Order By: Relevance
“…In any case, the bioreactor fatigue test system presented here represents a reasonable methodology for the study of the role of cyclic loading on biofilm colonization, proving that the combination of cyclic loading and bacterial exposure assists secondary caries propagation. Furthermore, it will also be useful for evaluating new restorative materials (e.g., such as those described in [40]) that are intended to slow or prevent secondary tooth decay.…”
Section: Resultsmentioning
confidence: 99%
“…In any case, the bioreactor fatigue test system presented here represents a reasonable methodology for the study of the role of cyclic loading on biofilm colonization, proving that the combination of cyclic loading and bacterial exposure assists secondary caries propagation. Furthermore, it will also be useful for evaluating new restorative materials (e.g., such as those described in [40]) that are intended to slow or prevent secondary tooth decay.…”
Section: Resultsmentioning
confidence: 99%
“…The BAG surface is purposely not treated to allow it to be slowly dissolved in a body fluid in order to release potentially beneficial ions. It has been shown that this process does not reduce the physical properties of the BAG or BAG-F composite during aging in media or bacteria for up to two months compared to the control composite [2]. However, the surface properties of the composite with BAG are likely affected due to the dissolution, especially in the face of a bacterial challenge which may represent an extrinsic factor that can alter the surface appearance.…”
Section: Discussionmentioning
confidence: 99%
“…New dental composites are being developed with bioactive additives having the potential to render them less susceptible to oral bacteria and promoting of tooth remineralization [1,2]. These composites will be used in all areas of the mouth, and will therefore have the same requirement for initial and long term esthetics as current materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Because of its much greater surface area, sol-gel-derived BAG has the potential to more readily release these ions in composites, and be rechargeable when exposed to topical sources of calcium and fluoride. Furthermore, studies of composites formulated with BAG have shown that the mechanical properties are not significantly compromised by addition of 12 to 15 wt% BAG, [26,27] and the total material loss for a nonsilanated bioglass-contaning composite was not quite 1% after 60 days in DI water. [27]…”
Section: Introductionmentioning
confidence: 99%